Skull fractures in car accidents: Types and Causes - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Robert Czerski (Kazimierz Wielki University, 2018)
Brain injury may be the result of a sudden blow to the head or head impact. The result is damage at the site of application of force and damage of the remote location. The force acting on the head causes not only local effects through the oppression, but also puts in motion the head, which causes the cranial structures The aim of the study was to characterize head injuries with special attention to their types. After regaining consciousness, and coming out of immediate danger of life reveals a number of problems the nature of neurological, psychological and neuropsychological, the latter reveal the disorder is sometimes quite late due to their discrete nature A serious problem is post traumatic stress disorder in the form of fear, helplessness, feelings of constant threat. In extreme cases, they represent a permanent team apical or brain death occurs.